The effect of fiber angles on energy absorption of 50 partially wrapped aluminium-composite hybrid tube under axial crushing : Die Wirkung von Faserwinkeln auf die Energieabsorption von 50 teil-umhülltem Aluminium-Verbund-Hybridrohr unter axialer Stauchung - Abbas, T. (Wiley-VCH Verlag, 2017)
Hybrid tubes have several attractive definite properties like specific energy absorption and crush force efficiency. These tubes have applications in automobiles and aerospace industry. In this research, the circular aluminium tube is partially wrapped with E-glass/Epoxy composite, using filament winding technique, to produce a hybrid tube. The fiber orientations in partial wrapping are ±10°, ±55° and 90° to the tube axis. Four composite layers are used and 50 area of the aluminium tube is covered by composite in partial wrapping. The effect of fiber orientations on specific energy absorption and crush force efficiency under axial crushing is studied. Moreover, collapse modes of failure are also identified. The results indicate that ±55° fiber orientation is good in energy absorption and crush force efficiency. Moreover, specific energy absorption and crush force efficiency of partially wrapped the tube with ±55° fiber orientation are 45.61 and 58.08 more as compared with aluminium tube. © 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim